Faktor-Faktor Yang Mempengaruhi Risk Disclosure Dengan Pendekatan Stakeholder Theory Pada Perusahaan Manufaktur Di Bursa Efek Indonesia - Tri Irawati (Jurnal Ilmiah SINUS, 2012)
This study aims to examine the factors that influence risk disclosure with stakeholder theory approach to the manufacturing companies that present financial statements in the Indonesia Stock Exchange. The results are expected to provide empirical evidence of factors that influence the disclosure risk (leverage, institutional ownership, the ability to generate earnings and the proportion of tax payments) with the approach to stakeholder theory, as for the control variables used in this study profiles the company, size and firm age .This study sample consisted of 130 companies in Indonesia Stock Exchange (BEI) in 2008 and 2009. Research carried out by content analysis on the company's annual report and tested with multiple linear regression. The results of risk disclosure is at most financial risk and integrity risk, information and technology risk, strategic risk, environmental risk, and operational risk. Leverage impact positively on the disclosure of risks to the significance of 0.1. Institutional share ownership, the ability to generate income, the proportion of tax payments does not affect positively on the disclosure of risk. Control variables that affect the disclosure of risk is the company's size and age profile while the company does not have an influence Key words   :   leverage, institutional ownership, the ability to generate earnings and the proportion of tax payments